Numerical Study on Bray-Liebhafsky Oscillatory Reaction: Bifurcations - Stanković, Branislav; Čupić, Željko; Pejić, Nataša; Kolar-Anić, Ljiljana (Journal of Applied Nonlinear Dynamics, 2026)
The time series obtained by numerical simulations of the model of the Bray-Liebhafsky oscillatory reaction is analyzed under the continuously fed well stirred tank reactor (CSTR) conditions, with the aim to find bifurcation points in which system of Bray-Liebhafsky oscillatory reaction transforms from stable to unsta- ble state and vice versa. Types of bifurcation points, supercrit- ical and subcritical Andronov-Hopf bifurcation and saddle-loop bifurcation are determined from characteristic scaling laws.